The Influence of Use of Internet Media and Textbooks on Student Learning Outcomes in Accounting Class of Vocational High Schools - Suranto, S; Rahmawati, Defi (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to examine the effect of internet media utilization and textbooks on student learning outcomes in Basic Accounting class X AKL SMK Negeri 1 Sragen. This research is a quantitative study with a survey design. The population in this study were all students of class X AKL SMK Negeri 1 Sragen in the 2022/2023 academic year. The sample was taken as many as 118 students with simple random sampling. Data collection methods using questionnaires and documentation. The data analysis technique used is multiple linear regression analysis, t test, F test, determination coefficient test, effective contribution (SE) and relative contribution (SR). The results of this study indicate that: 1) Internet Media Utilization has a positive and significant effect on student learning outcomes. This is known on the basis of the calculation obtained of 8.752 > 1.980 with a significance value < 0.05, namely 0.000; 2) Textbook utilization has a positive and significant effect on learning outcomes. This is known on the basis of the calculation obtained of 9.626 > 1.980 with a significance value < 0.05, namely 0.000; and 3) Internet media utilization and textbooks simultaneously affect learning outcomes. This is known on the basis of the calculation obtained of 96.665 > 3.08 with a significance value < 0.05, namely, 0.000. The implications of this research can be used by the school to hold seminars on the utilization of internet media and textbooks to support learning activities and improve student learning outcomes at SMK Negeri 1 Sragen.